Revisiting the Teleost Thymus: Current Knowledge and Future Perspectives - Imarai-Bahamonde, C; Maisey-Munoz, K; Barraza-Rojas, F; Wong-Benito, V (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The thymus in vertebrates plays a critical role in producing functionally competent Tlymphocytes. Phylogenetically, the thymus emerges early during evolution in jawed cartilaginous fish, and it is usually a bilateral organ placed subcutaneously at the dorsal commissure of the operculum. In this review, we summarize the current understanding of the thymus localization, histology studies, cell composition, and function in teleost fishes. Furthermore, we consider environmental factors that affect thymus development, such as seasonal changes, photoperiod, water temperature fluctuations and hormones. Further analysis of the thymus cell distribution and function will help us understand how key stages for developing functional T cells occur in fish, and how thymus dynamics can be modulated by external factors like photoperiod. Overall, the information presented here helps identify the knowledge gaps and future steps needed for a better understanding of the immunobiology of fish thymus. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.